Pengaruh Atribut Produk Terhadap Keputusan Pembelian Mie Sedaap Selection Korean Spicy Soup Di Ponorogo - Bagus Pujianto; Suyono Suyono (Jurnal Kajian Ilmu Manajemen (JKIM), 2021)
This study aims to determine the effect of product attributes consisting of Brand, Quality, Features, Design on the purchase decision of Mie Sedaap Selection Korean Spicy Soup steamed layer buyers in Ponorogo.  Sampling in this study using accidental sampling and analyzed using multiple linear regression analysis.  The results of this study indicate that the product attributes partially have a positive and significant effect on purchasing decisions, except for the brand variable.  And product attribute variables simultaneously have a positive and significant effect on purchasing decisions.